Short-day treatment in late summer reduces the chilling requirement in Norway spruce seedlings - Partanen, Jouni; Häkkinen, Risto; Viherä-Aarnio, Anneli; Stenvall, Niina; Hänninen, Heikki (Suomen metsätieteellinen seura, 2026)
Artificial shortening of photoperiod with short-day (SD) treatment in late summer is a common measure in forest nurseries to advance the growth cessation and increase the frost hardiness of seedlings in the autumn. We conducted an experimental study of the effect of SD treatment (12 h) in the preceding summer and the photoperiod (16 h, 8 h) prevailing in the regrowth test under forcing conditions. The effect of these factors on the chilling requirement in second-year Norway spruce Picea abies (L.) Karst. seedlings was studied. Half of the seedlings were first subjected to a three-week SD treatment between 11 July and 1 August 2005, whereas the other half were used as the control group. The seedlings were first exposed to chilling in natural conditions. Subsequently, samples of the seedlings were transferred at intervals between September and May to a regrowth test in growth-promoting forcing conditions in a greenhouse. Additionally, we observed the bud burst of the seedlings in natural conditions during the next spring. Our main result was that SD treatment reduced the chilling requirement in the seedlings. Long photoperiod (16 h) in the forcing conditions also reduced the chilling requirement. The buds of the SD-treated seedlings burst earlier than those of the control seedlings and generally at almost the same time in both photoperiods. This suggests that the photoperiod prevailing in the forcing conditions has no additional delaying or advancing effect on the bud burst of SD-treated seedlings. In natural outdoor conditions, the SD treatment in the preceding summer advanced the springtime bud burst slightly.
Keywords: bud burst percentage; days to bud burst; rest; endodormancy release; forcing; quiescence; Norway spruce; seedlings